(untitled) - Du Plessis, Le Roi Alexander

Integrated optical tweezers and microfluidic system for live cell fluorescence spectroscopy to monitor cellular response (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.